Determinants of birth registration in sub-Saharan Africa: evidence from demographic and health surveys - Richard Gyan Aboagye; Joshua Okyere; Joshua Okyere; Abdul-Aziz Seidu; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Bright Opoku Ahinkorah; Eugene Budu; Sanni Yaya (Frontiers in Public Health, 2023)
BackgroundBirth registration is a crucial aspect of ensuring that children have access to their rights and benefits, including health care, education, and citizenship. In sub-Saharan Africa (SSA), birth registration rates remain low, with millions of children going unregistered each year. Understanding the predictors of birth registration among children in this sub-region is important for developing targeted interventions to improve registration rates. The study examines the predictors of birth registration among children in SSA.MethodsWe performed a cross-sectional analysis of secondary data pooled from the Demographic and Health Survey of 17 countries conducted from 2015 to 2021. A weighted sample of 162,500 children was included in the final analysis. We summarized the proportion of birth registration among children in SSA using a forest plot. We utilized a multilevel binary logistic regression analysis to examine the predictors of birth registration. The results were presented using adjusted odds ratios (aOR) with 95% confidence intervals (CIs).ResultsWe found that 48.32% [48.15–48.49] of births in SSA were registered. The lowest and highest prevalence of birth registration were found in Ethiopia (2.70 [2.38–3.02]) and Sierra Leone (92.93 [92.36–93.50]), respectively. Increasing child’s age was found to be significantly associated with a higher likelihood of birth registrations, with those aged 4 years [aOR = 1.55; CI = 1.49, 1.62] having the highest odds of birth registration compared to those aged below 1 year. Children born to mothers with primary [aOR = 1.17; CI = 1.11, 1.24], secondary [aOR = 1.44; CI = 1.34, 1.54], and higher education [aOR = 1.71; CI = 1.48, 1.99] were more likely to be registered than those born to mothers who had no formal education. Also, children born in health facilities were more likely to be registered [aOR = 1.60; CI = 1.48, 1.74] than those born at home. The odds of birth registration were significantly higher among children whose mothers received assistance during delivery [aOR = 1.88; CI = 1.72, 2.04], those in the richest wealth index [aOR = 3.91; CI = 3.54, 4.33], and those in rural areas [aOR = 1.92; CI = 1.76, 2.10].ConclusionThere is low childbirth registration coverage in SSA. The predictors of this phenomenon are the child’s age, maternal level of education, wealth index, place of residence, sub-region, maternal age, place of delivery, assistance during delivery, marital status, and sex of household head. Interventions and policies developed to improve childbirth registration coverage in SSA should prioritize mothers with no formal education, those who deliver at home, those with low socioeconomic status, those living in female headed household, and adolescent mothers.